A case study on environmental factors affecting user traffic at the College of Arts and Letters library - Mararac, Caren Cyel G. (2015)
Many factors need to be present in a specific library environment to achieve maximum efficiency in meeting its users' needs. Several other factors influence the users' intention to enter and stay in the library. This study focused on the environmental factors affecting user traffic at the College of Arts and Letters Library.